EFFECTS OF RECREATIONAL PHYSICAL ACTIVITIES ON WOMEN'S MENTAL AND PHYSICAL HEALTH DURING THE PANDEMIC CAUSED BY THE CORONAVIRUS (COVID 19) - Jasmin Bilalić,; Osman Lačić,; Zada Tomić,; Berina Pezerović,; Sanja Mujkanović Mujezinović,; Nevres Muminović,; Sanjin Hodžić, (Sport Scientific And Practical Aspects, 2025)
The aim of the research is to determine the effects of the pandemic caused by the Coronavirus (COVID-19) on the mental and physical health of young adult women, using standardized instruments for the assessment of mental and physical health. The sample of 40 women was selected into two groups according to the continuity of recreational physical activity during the pandemic caused by the Coronavirus. An increase in symptoms of depression and anxiety was recorded in both groups during the pandemic, but it could be noted that respondents from the discontinuous level of physical activity group recorded a higher degree of depression and anxiety compared to respondents from the continuous level of physical activity group. In terms of physical health, respondents who continued physical activity maintained relatively stable physical health results during the pandemic, while respondents who did not maintain continuity of work showed significantly worse results compared to the period before the pandemic. Thus, regular physical activity is associated with better mental and physical health during the pandemic caused by the Coronavirus (COVID-19). Overall, this research emphasizes the importance of maintaining regular recreational activities, even during crisis situations, as a key factor for preserving psychophysical health.